2009
DOI: 10.1097/icl.0b013e3181a20361
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Short-Term Evaluation of Presbyopic Contact Lens Performance

Abstract: Early assessment is relatively unrepresentative of performance later on during multifocal contact lens wear. Acuity based measures of vision remain substantially unchanged over the medium term, apparently because these metrics are insensitive indicators of performance compared with subjective alternatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
55
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 7 publications
7
55
1
Order By: Relevance
“…This study was limited by the small adaptation period. While this imitates what often occurs when patients first fit multifocal contact lenses in practice, changes in lens performance may occur over 4-15 days (9,22) . Longer term studies are required to determine if these study measures continue to predict performance over a longer period of time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study was limited by the small adaptation period. While this imitates what often occurs when patients first fit multifocal contact lenses in practice, changes in lens performance may occur over 4-15 days (9,22) . Longer term studies are required to determine if these study measures continue to predict performance over a longer period of time.…”
Section: Discussionmentioning
confidence: 99%
“…Papas et al pre viously reported that objective findings have little value for this purpose, and clinicians should rely on subjective findings to predict success (9) . We found that patients with better HCVA at intermediate, and occasionally near, distances tended to have higher satisfaction with overall vision, which in turn was a factor that influenced the patients' willingness to buy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering participant lifestyle, contact lens preference was not dependent on whether participants frequently drove, used a computer, cooked, shopped, used a mobile phone, watched Poor subjective visual satisfaction due to visual fluctuations, inadequate visual quality, halos and ghosting are commonly cited as reasons for presbyopic contact lens rejection [4,28]. Indeed, a trend emerged in the present investigation for some multifocal lens type preference to align with the lens offering the best distance visual acuity after 4 weeks of wear.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, data suggest it is unwise to rely on initial consulting room tests to predict the success of presbyopic contact lens options [3,4], at least for older designs. Therefore, the utility of additional indicators, clinical and/or non-clinical, to aid the initial selection of the optimum presbyopic lens would be beneficial, reducing the presbyopic contact lens drop-out rate and minimising chair time.…”
Section: Introductionmentioning
confidence: 99%